Effects of the constructed wetland on dissolved organic matter properties in the drainage channel of domestic sewage treatment plant in winter. Issue 1 (February 2021) - Yu, Hanxia; Luo, Xiao; Ma, Lina; Tan, Wenbing
Abstract: As a low investment and low energy consumption wastewater treatment technology, the constructed wetland has been gradually accepted by the world. However, there is still a lack of systematic assessment on the impact of the constructed wetland on dissolved organic matter (DOM) properties in the drainage channel of domestic sewage treatment plant in winter. In this study, 3D excitation-emission matrix fluorescence spectroscopy and ultraviolet spectroscopy were combined to reveal the evolution process of DOM properties in the constructed wetland in winter. The results showed that DOC contributed more than 55% of COD in the drainage channels of Shijiazhuang domestic sewage treatment plant in winter, but the COD was significantly decreased after treated by the constructed wetland, which was mainly caused by the more extensive degradation of elements N, H, S and P in DOM. In addition, water DOM in the constructed wetland in winter was mainly contributed by microorganisms, and humus-like components in water DOM were more easily degraded than protein-like components. And humus-like components gradually transformed into protein-like components in the degradation process, and fulvic-like and humic-like components had the same decomposition fate in the constructed wetland in winter.